2003
DOI: 10.1046/j.1440-0960.2003.00641.x
|View full text |Cite
|
Sign up to set email alerts
|

O'Brien's actinic granuloma in association with prolonged doxycycline phototoxicity

Abstract: O'Brien's actinic granuloma is clinically characterized by annular papules and plaques on sun-exposed areas of skin. These lesions often occur insidiously on a background of severe solar elastosis; however, an acute variant following sunburn has been reported in the literature. We present two cases of acute actinic granuloma precipitated by episodes of sunburn occurring on a background of prolonged doxycycline phototoxicity. Biopsies from both patients showed a histiocytic infiltrate with multinucleate giant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 17 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…4 This predominance is also found in other dermatoses in which there is an abnormal response to ultraviolet radiation such as polymorphic light eruption and photosensitivity to drugs. 7 Some authors have reported lesions resembling actinic granuloma in unexposed areas, i.e. areas with no solar damage.…”
Section: Discussionmentioning
confidence: 99%
“…4 This predominance is also found in other dermatoses in which there is an abnormal response to ultraviolet radiation such as polymorphic light eruption and photosensitivity to drugs. 7 Some authors have reported lesions resembling actinic granuloma in unexposed areas, i.e. areas with no solar damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, minocycline should be used with care, as it may be associated with photosensitivity. This could potentially worsen, rather than improve AEGCG, as previously reported with doxycycline (12).…”
Section: Case Reportmentioning
confidence: 59%
“…Also, photo-onycholysis is possible [5,6,7,8]. Lichenoid reaction and actinic granuloma were reported in only 1 case each [9,10]. …”
Section: Discussionmentioning
confidence: 99%
“…To determine the frequency or risk of phototoxic reactions in the course of a therapy with doxycycline is difficult because it depends on the geographical location of the country in which the patient stays, the patient's behavior referring to sun exposure, and also the sunscreen preparation used, if at all [10,13]. Moreover, the term “phototoxic reaction” is not consistently used in publications and varies from sunburn-like sensation with light erythema to heavy manifestation with large-area erythematous plaques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation